Distal renal tubular acidosis and sensorineural deafness with mutation in the ATP6V1B1 gene - Periquito,Isabel (2013)
Distal renal tubular acidosis is a rare disorder characterized by the inability in acidification of urine, conditioning hyperchloraemic acidosis, hypokalaemia, hypercalciuria and nephrocalcinosis, which can cause growth retardation, abnormal bone metabolism and, when untreated, chronic renal failure. Distal renal tubular acidosis and sensorineural deafness is an autosomal recessive disease caused by mutations in the gene encoding B1 subunit of H+ -ATPase (ATP6V1B1). The authors report the cases of two sisters who presented failure to thrive, changes in ionic and acid-base balance and sensorineural deafness. A homozygous mutation in ATP6V1B1 gene was detected in both girls. These two cases are intended to highlight the importance of an early diagnosis in this rare disease